Building a magnetic culture : how to attract and retain top talent to create an engaged, productive workforce - Sheridan, Kevin, 1960- (New York, NY. : McGraw-Hill)
What is a magnetic culture and what are the bottom line benefits of employee engagement? -- Engagement is a two-way street: eight steps for creating an environment of shared engagement -- The top 10 engagement drivers -- Recruiting: the foundation of a magnetic culture -- Overcoming demagnetizers: compensation and other challenges for managers -- Do not ignore diversity -- Engagement trends -- Taking action toward engagement -- Conclusion: the ultimate summit - engagement.